Penggunaan Bahasa dalam Proses Pembuatan Rumah Tradisional sebagai Pengungkap Pola Pikir Kelompok Etnik Bantik di Minahasa (Suatu Kajian Linguistik Antropologi) - Lumempouw, Femmy (Universitas Sam Ratulangi, 2016)
This research is an attempt to find out about the traditional house making as the Minahasan Bantik ethnic ways of thinking. The aims of the research are: (1) to identify and classify the house making process; (2) to identify and classify the utterances, idioms , and discourses in traditional haouse architecture which has Minahasan Bantik ethnic; and (3) to explain the language unit. The method used in this research is descriptive qualitative. The technique is observation and interview. The data is analyzed by using SPEAKING ethnography scheme from Hymes. The result shows that the Minahasan Etnic bantik has way of thinking in area of life, religion, farming, and kinship. Keywords: local wisdom, way of thinking, houase architecture, Minahasan